Outcomes of Multimodality In situ Recanalization in Hybrid Operating Room (MIRHOR) for symptomatic chronic internal carotid artery occlusions. (4th January 2019) - Jiang, Wei-jian; Liu, Ao-Fei; Yu, Wengui; Qiu, Han-Cheng; Zhang, Yi-Qun; Liu, Fang; Li, Chen; Wang, Rong; Zhao, Yuan-Li; Lv, Jin; Li, Tian-Xiao; Liu, Ce; et al.
Abstract : Background: An in situ recanalization procedure of endovascular therapy (ET) or carotid endarterectomy (CEA) has been attempted in patients with symptomatic chronic internal carotid artery occlusions (ICAOs), though the recanalization rates of both are low. Objective: To investigate the outcomes of Multimodality In situ Recanalization for ICAOs in a Hybrid Operating Room (MIRHOR) at the same session. Methods: Symptomatic chronic ICAOs were classified into type A or B (short occlusion with or without a tapered residual root [TRR]), and C or D (long occlusion with or without TRR), and managed in a hybrid operating room with ET, CEA, or both, as needed. Primary efficacy outcome was technical success of recanalization with Thrombolysis in Myocardial Infarction 3. Secondary efficacy outcome was any stroke or death within 30 days (primary safety outcome) plus an ipsilateral ischemic stroke after 30 days. Results: Technical success was finally achieved in 35 (83.3%) of 42 consecutively enrolled patients with ICAO, which was significantly higher than 35.7% (15/42, p<0.001) from the initial ET or CEA alone. Furthermore, the success rate was in descending order: 100% (18/18) for type A and B occlusions, 75% (6/8) for type C occlusions, and 69% (11/16) for type D occlusions (p=0.017). Two secondary efficacy outcome events (5.1%) without mortality, including one (2.4%) primary safety outcome, were observed during a mean follow-up of 10.5 months. Conclusion: The MIRHOR for symptomatic chronic ICAOs at the same session significantly improves technical success, with low periprocedural complications and favorable clinical outcomes. The ICAO classification appears valuable in predicting technical success.